(untitled) (Innovation & Development in Engineering and Applied Science, 2020)
Actually it is very common to use cosmetic hand prostheses. However, these devices have poor functionality, therefore the amputated patient does not get normal development in everyday tasks. It is important to remark that these prostheses are very expensive. This work proposes the right hand mechanical design for a patient with wrist disarticulation to be controlled using myoelectric signals. Some mechanicals designs phases where considered; first the palm, second the fingers, third the motor system and fourth the solution validation using the finite element method (Inventor-Autodesk software). The results indicate that solution have the capacity to make the basic fingers movements, such as: flexion-extension.